A study of dyslipidemias in newly diagnosed hypertensive patients - Arangi, Pallavi; Medabalimi, Rajya Lakshmi; Acharya, Anand (International Journal of Research in Medical Sciences, 2020)
Background: Dyslipidemia and hypertension are a major, common and modifiable risk factor for diseases like a stroke; coronary artery disease etc. which are common causes for mortality in India. Dyslipidemia and hypertension are usually found co-exist, which accelerates the process of atherosclerosis. Methods: It is a cross-sectional study conducted on the patients who are newly diagnosed hypertensive visited Medical OPD in Konaseema institute of medical sciences between January 2018 to June 2019. All were investigated for various clinical parameters on lipid profile abnormalities. Results were compared among cases and controls. Results: A total number of patients included in the study were 167,107 are cases and 60 controls. Significant higher levels of total cholesterol, triglycerides, LDL-c and lower levels of HDL-c were observed in hypertensive patients with p-value significant <0.0001. Conclusions: Hypertensive patients have significantly elevated levels of all forms of cholesterol and a higher percentage of individuals in the dyslipidemic state when compared with normotensive patients. Pre-diabetic state significantly increases the total cholesterol in hypertensive patients.